Carer and service providers' experiences of individual funding models for children with a disability in rural and remote areas. (3rd May 2013) - Dew, Angela; Bulkeley, Kim; Veitch, Craig; Bundy, Anita; Lincoln, Michelle; Brentnall, Jennie; Gallego, Gisselle; Griffiths, Scott
Abstract There is a global movement for people with a disability towards person‐centred practices with opportunities for self‐determination and choice. Person‐centred approaches may involve individual funding (IF) for the purchase of required support. A shift to a person‐centred model and IF should allow people with a disability and their carers greater choice in therapy access. However, individuals who live in rural and remote areas have less choice and access to therapy services than their metropolitan counterparts. Drawing on data from a larger study into therapy service delivery in a rural and remote area of New South Wales, Australia, this study describes some benefits and barriers to using IF to access therapy services in rural areas. Ten carers and 60 service providers participated in audio‐recorded focus groups and individual interviews during which IF was discussed. Transcribed data were analysed using thematic analysis and constant comparison. Greater access to and choice of therapy providers were identified as benefits of IF. Four barriers were identified: (i) lack of information and advice; (ii) limited local service options and capacity; (iii) higher costs and fewer services and (iv) complexity of self‐managing packages. A range of strategies is required to address the barriers to using IF in rural and remote areas. Carers indicated a need for: accessible information; a local contact person for support and guidance; adequate financial compensation to offset additional travel expenses and coordinated eligibility and accountability systems. Service providers required: coordinated cross‐sector approaches; local workforce planning to address therapist shortages; certainty around service viability and growth; clear policies and procedures around implementation of IF. This study highlights the need for further discussion and research about how to overcome the barriers to the optimal use of an IF model for those living in rural and remote areas.